2020
DOI: 10.3390/ma13071778
|View full text |Cite
|
Sign up to set email alerts
|

On the Microstructure and Properties of Nb-12Ti-18Si-6Ta-2.5W-1Hf (at.%) Silicide-Based Alloys with Ge and Sn Additions

Abstract: In this paper two Nb-silicide-based alloys with nominal compositions (at.%) Nb-12Ti-18Si-6Ta-2.5W-1Hf-2Sn-2Ge (JZ1) and Nb-12Ti-18Si-6Ta-2.5W-1Hf-5Sn-5Ge (JZ2) were studied. The alloys were designed using the alloy design methodology NICE to meet specific research objectives. The cast microstructures of both alloys were sensitive to solidification conditions. There was macro-segregation of Si in JZ1 and JZ2. In both alloys the βNb5Si3 was the primary phase and the Nbss was stable. The A15-Nb3X (X = Ge,Si,Sn) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(71 citation statements)
references
References 39 publications
2
69
0
Order By: Relevance
“…Similarly, with the research described in [ 14 ], we found it very difficult to make an alloy with composition as close as possible to the nominal one, owing to loss by evaporation of elements with low melting points. In the same way as in [ 14 ], we made up for the elemental losses by slightly increasing the weight of lost elements. After many attempts, the “best” two alloys were selected for further study (see Section 2.2.2 ).…”
Section: Methodssupporting
confidence: 83%
See 4 more Smart Citations
“…Similarly, with the research described in [ 14 ], we found it very difficult to make an alloy with composition as close as possible to the nominal one, owing to loss by evaporation of elements with low melting points. In the same way as in [ 14 ], we made up for the elemental losses by slightly increasing the weight of lost elements. After many attempts, the “best” two alloys were selected for further study (see Section 2.2.2 ).…”
Section: Methodssupporting
confidence: 83%
“…The microstructure of the bottom of the button was finer ( Figure 5 c) where the (Nb,W) ss and HfO 2 exhibited white contrast. The solubility of Ta in the (Nb,W) ss was high (15.2 at.%) and the Si content was low (1.7 at.%), see Table S3 , compared with the Nb ss in the as cast alloys JZ1 and JZ2 [ 14 ] and JZ3-AC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations